2010
DOI: 10.1021/nn1016605
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-Functionalized Silver Nanoparticles for the Naked Eye Detection of Aromatic Isomers

Abstract: We report herein the development of a highly robust, quantitative, sensitive, and naked eye colorimetric detection method for different isomers of aromatic compounds using β-CD-modified silver nanoparticle (AgNPs) probes. This assay relies on the distance-dependent optical properties of Ag nanoparticles and the different inclusion binding strength of the aromatic guests to β-CD host. In the presence of different isomers of aromatic compounds, AgNPs could be rapidly induced to aggregate, thereby resulting in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
72
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(73 citation statements)
references
References 28 publications
1
72
0
Order By: Relevance
“…One of the main sources of variability is the material of which these Figure 1. Current strategies for in-field detection of analytes; (A) Quantitative electrochemical detection with disposable electrodes and electronic readers (glucose meter) (reproduced from [10] with permission from the Royal Society of Chemistry); (B) Naked-eye detection with paper-based substrates: detection of histone methylation as a function of the amount of histone extract (reproduced from [20] with permission from the American Chemical Society); (C) Solution-based detection of analytes with the naked eye: specific detection of tryptophan alone (C) or in the presence of other 9 amino acids (D), that do not generate a signal by themselves (B) (reproduced from [21] with permission from Willey-VCH); (D) Solution-based detection of analytes with nanoparticles: detection of aromatic isomers with cyclodextrin-modified silver nanoparticles; top: phenol (ii), pyrocatechin (iii), hydroquinone (iv), resorcinol (v); bottom: aniline (ii), o-phenylenediamine (iii), p-phenylenediamine (iv), and mphenylenediamine (v) (reproduced from [31] with permission from the American Chemical Society). devices are fabricated: different paper substrates have different flow speeds, which are crucial to determine the sensitivity and specificity of the analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main sources of variability is the material of which these Figure 1. Current strategies for in-field detection of analytes; (A) Quantitative electrochemical detection with disposable electrodes and electronic readers (glucose meter) (reproduced from [10] with permission from the Royal Society of Chemistry); (B) Naked-eye detection with paper-based substrates: detection of histone methylation as a function of the amount of histone extract (reproduced from [20] with permission from the American Chemical Society); (C) Solution-based detection of analytes with the naked eye: specific detection of tryptophan alone (C) or in the presence of other 9 amino acids (D), that do not generate a signal by themselves (B) (reproduced from [21] with permission from Willey-VCH); (D) Solution-based detection of analytes with nanoparticles: detection of aromatic isomers with cyclodextrin-modified silver nanoparticles; top: phenol (ii), pyrocatechin (iii), hydroquinone (iv), resorcinol (v); bottom: aniline (ii), o-phenylenediamine (iii), p-phenylenediamine (iv), and mphenylenediamine (v) (reproduced from [31] with permission from the American Chemical Society). devices are fabricated: different paper substrates have different flow speeds, which are crucial to determine the sensitivity and specificity of the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…1D). [23][24][25] A key factor for the development of complex sensing approaches is that these nanomaterials can be decorated with myriads of biomolecules, [26][27][28] polymers 29 and macrocycles 30,31 that confer them specific recognition capabilities for the detection of a wide array of molecules. For example, nanoparticle aggregates linked by peptides can be used for the one-step detection of proteases when the protease activity triggers the dispersion of the nanoparticle collectives.…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles have obtained increasing attention in the past decade due to their attractive electric [25,26], optical [27,28], catalytic [29,30], and particularly antimicrobial properties [31,32] that are well established and extensively investigated mainly in colloidal systems. Nevertheless, many practical applications of silver nanoparticles require their entrapment on different substrates and matrices [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…These applications require appropriate chemical functionalization of the nanoparticles with organic molecules or their incorporation into polymer matrices (Dallas, Sharma, Zboril, 2011). Among the numerous types of nanoparticles that have been used to decorate polymers, silver nanoparticles (AgNPs) are the most researched, due to their electronic properties (Líu et al, 2010;Tricoli, Pratsinis, 2009;Chen et al, 2010), and optical (Zeng et al, 2007), catalytic (Severin et al., 2007; Signori et al, 2010) and antimicrobial activities (Panacek et al, 2006;Kvitek et al, 2008;Prema, Raju, 2009;Chaloupka, Malam, Seifalian, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These applications require appropriate chemical functionalization of the nanoparticles with organic molecules or their incorporation into polymer matrices (Dallas, Sharma, Zboril, 2011). Among the numerous types of nanoparticles that have been used to decorate polymers, silver nanoparticles (AgNPs) are the most researched, due to their electronic properties (Líu et al, 2010;Tricoli, Pratsinis, 2009;Chen et al, 2010), and optical (Zeng et al, 2007), catalytic (Severin et al., 2007; Signori et al, 2010) and antimicrobial activities (Panacek et al, 2006;Kvitek et al, 2008;Prema, Raju, 2009;Chaloupka, Malam, Seifalian, 2010).Recently, there has been increasing interest in studying nanostructured biopolymers with antimicrobial characteristics for their immense potential use in devices that require a high antiseptic character. Recent studies have shown that an especially lucrative opportunity lies in applying these polymeric nanostructures in the medical field (Abdelgawada, Hudsona, Rojas, 2014;Chaloupka, Malam, Seifalian, 2010;Dallas, Sharma, Zboril, 2011).…”
mentioning
confidence: 99%